Pemahaman Geometri Danau Tondano melalui Pendekatan Batimetri dan Morfometrik - Kumaat, Jocye Christian; Tumengkol, Aghata Archenta; Liuw, Chistian Beckham (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
In order to understand the geometric characteristics of Lake Tondano and to obtain a comprehensive picture of the lake's geomorphological structure and dynamics, this study utilized various descriptive-analytical approaches. These approaches included hydrographic surveys, spatial analysis techniques, bathymetry, and morphometrics. The bathymetric analysis of Lake Tondano reveals a maximum depth of 30.22 meters, with a total water volume of 590,647,445.7 m³. Morphometric analysis yielded a maximum length of 11,024.75 meters, a maximum width of 2,940.01 meters, a surface area of 45,434,418.9 m², and a circumference length of 43,121.56 meters. The results indicate that the contour map and 3D visualization depict detailed information regarding depth variations and bottom topography. The average depth of 13.00 meters exerts a substantial influence on water productivity and nutrient distribution. The volume development (VD) value of 1.29 suggests that Lake Tondano is a shallow lake with a flat bottom.This research underscores the necessity for regular monitoring of water volume changes to comprehend ecosystem dynamics and the impacts of human activities. The study's findings underscore the significance of a comprehensive understanding of morphometric parameters and water volume in managing water resources, formulating conservation policies, and advancing research in aquatic ecology within Lake Tondano.